Perfil químico e potencial farmacológico de nanoemulsões do óleo essencial de Ocimum campechianum Mill (ALFAVACA) - SOUZA, Franscristhiany Silva (2023)
Ocimum campechianum (OC) is an aromatic plant rich in essential oils (EOs) with proven pharmacological effects. Its direct application is limited, due to the characteristics inherent to EOs, such as degradation, volatility, and low solubility, making it necessary to apply technologies that preserve their physical and pharmacological properties. This study aimed to evaluate the chemical profile, toxicity, and physicochemical properties of Ocimum campechianum essential oil (OEOC), in addition to producing, characterizing, and evaluating the antimicrobial and antioxidant effect of its oil-in-water nanoemulsions (NEs) (O/ A). The plant species was collected in the rural area of the city of São Luís - MA (Brazil). The EO and volatiles from the OC leaves were extracted by hydrodistillation (HD) and static headspace (HS) techniques, respectively, and analyzed by gas chromatography coupled to a mass spectrometer (GC/MS and HS-GC/MS). The physicochemical properties and toxicity of OEOC were determined. NEs were prepared using a low-energy phase inversion emulsification method, with each formulation composed of OEOC, non-ionic surfactant Tween 80 (T80), and water (H2O). A factorial design (DCCR 22 ) based on response surface methodology (MSR) was used to optimize the concentrations of the components, resulting in eleven NEs. The most stable NEs (NE4-OEOC and NE5-OEOC) were selected and evaluated for stability by centrifugation, temperature (4oC and 25oC), macroscopic test and physicochemical characterization, including droplet size, zeta potential, polydispersity index (PDI), pH, turbidity and morphology by atomic force microscopy (AFM). OEOC and NEs were investigated for their antioxidant (DPPH method) and antimicrobial (disk diffusion and broth microdilution methods) effects against fungi (Aspergillus Niger and Colletotrichum gloeosporioides) and bacteria (Staphylococcus aureus, Streptococcus mutans, Escherichia coli, Pseudomonas aeruginosa and Salmonella sp). The chemical profile of the OEOC revealed thirty-six compounds and the volatile fraction of fresh leaves twenty-four, being eugenol (48.62% and 21.48%) and β-caryophyllene (17.26% and 21.30%) the main ones, respectively. The OEOC presented a yield of 1.40%, intense clove aroma, slightly yellowish color and low toxicity against Artemia salina (LC50 = 955 mg. L-1). The selected NEs, NE4-OEOC and NE5-OEOC, showed stability over time without significant changes, evidenced in macroscopic tests, centrifugation, temperature (4oC and 25oC), spherical morphology of the drops, in addition to physical-chemical characterization with results initial zeta potential (-15.30 ± 0.40 mV and -6.86 ± 0.84 mV), droplet size (115.97 ± 0.69 nm and 30.81 ± 5.56 nm), PDI (0.28 ± 0.00 and 0.15 ± 0.04) with distribution characteristics of monodisperse particles (< 0.3), pH (6.10 ± 0.01 and 5.61 ± 0.01) and turbidity (0.56 ± 0.00 to 0.15 ± 0.00), respectively. The nanoemulsified EO, in both NEs, showed high antioxidant activity. As for antimicrobial activity, it revealed a bactericidal effect against the bacteria investigated, except for the NE5-OEOC formulation with a lower concentration of essential oil (1.98%), which did not inhibit Streptococcus mutans; in addition to fungicidal effect against Colletotrichum gloeosporioides. The results obtained were satisfactory and suggest that nanoemulsions of Ocimum campechianum essential oil have potential application in the pharmaceutical, agricultural, cosmetic and food areas as antimicrobial and antioxidant bioproducts.